Crypto assets and CBDCs in Latin America and the Caribbean: Opportunities and risks - Olga Bespalova; Maximiliano Appendino; Rina Bhattacharya; Jean Francois Clevy Aguilar; Nan Geng; Takuji Komatsuzaki; Justin Lesniak; Weicheng Lian; Sandra Marcelino; Mauricio Villafuerte; Yorbol Yakhshilikov (Latin American Journal of Central Banking (LAJCB), 2025)
After providing a general overview of the nature, pros, and cons of crypto assets and CBDCs, this paper focuses on documenting their recent experience in LAC. The region records a high interest in unbacked crypto assets and stablecoins and its authorities' policy responses have varied substantially, ranging from the introduction of Bitcoin as legal tender in El Salvador to their prohibition in many other countries worried about their impact on financial stability, currency/asset substitution, tax evasion, corruption, and money laundering. This paper also describes briefly the results of a survey on CBDCs' introduction plans and crypto assets regulation. Finally, this paper presents some general lessons and policy recommendations for the region on the regulation of crypto assets, digital currencies and cross-border payments, and on the potential introduction of CBDCs.
Keywords: E00; E42; E51; E52; E58; G20; O16; O30; O54; 330; Central Bank Digital Currency (CBDC); Central banking; Crypto assets; Cybersecurity; Digital currency; E-money; Financial supervision; Fintech; Latin America and Caribbean (LAC); Monetary policy; Money; Payment systems